Drug Use and Suicidality Among Asian American Women Who Are Children of Immigrants. (6th December 2013) - Hahm, Hyeouk Chris; Jang, Jisun; Vu, Cecilia; Alexander, L. Melissa; Driscoll, Kelsie E.; Lundgren, Lena
<x xml:space="preserve">Abstract</x> This study investigates the association between drug use and lifetime suicidal behaviors among Asian American women (n = 720) residing throughout Massachusetts, using data collected from 2010 to 2011. Logistic regression models identified that a history of hard drug use alone or in combination with soft drug use has a significant association with both suicidal ideation and suicide attempts among Asian American women, adjusting for demographic covariates, history of psychiatric diagnosis, and family communication. These findings highlight the importance of addressing hard drug use when designing suicide prevention programs for Asian American women.